What is “A Certain International Criminal Court” and does the Choice of a Fully International or Internationalized (Hybrid) Court/Chambers Matter for the Crime of Aggression Committed Against Ukraine? (Polish Yearbook of International Law, 2024)
When the International Court of Justice issued its Arrest Warrant Judgment in 2002, it indicated that personal immunities do not prevent proceedings in front of “certain international criminal courts” and provided three demonstrative examples of such courts.After the full-scale invasion of Ukraine commenced in February 2022, debates ensued regarding the elements necessary to qualify a court within the meaning of the Arrest Warrant Judgment. They particularly concern two types of tribunals (“fully international” and “hybrid / internationalized”). This article suggests that only fully international courts qualify as “certain international criminal courts”, while hybrid tribunals are far too attached to the sovereignty of State(s) to meet its criteria. The determination of a court as hybrid or international is rather fluid however, and the qualification as “a certain international criminal court” depends on various elements (the establishing mechanism; applicable law; and reflection of the will of the international community) in each individual case.